2015
DOI: 10.1080/19475411.2015.1129368
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable shape memory polymers based on epoxidized natural rubber cured by zinc ferulate via oxa-Michael reaction

Abstract: Although various shape memory polymers (SMPs) or diverse applications have been widely reported, the SMPs based on rubbers have been rarely realized due to the low triggering temperature of rubbers. In another aspect, the SMPs based on sustainable substances are highly desired for the growing shortage in fossil resources. In the present study, we accordingly developed the sustainable SMPs with tunable triggering temperature, based on natural rubber (NR) and ferulic acid (FA) as the raw materials. Specifically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…According to the above results, the curing rate and mechanical properties of MR y x -cured ENR are significantly higher than those of the previously reported ENR vulcanizates cured by new cross-linking methods (Figure ). Moreover, the curing and mechanical properties of MR y x -cured ENR could be facilely regulated via changing the structure and content of the cross-linkers, which could be able to meet industrial application requirements.…”
Section: Resultsmentioning
confidence: 99%
“…According to the above results, the curing rate and mechanical properties of MR y x -cured ENR are significantly higher than those of the previously reported ENR vulcanizates cured by new cross-linking methods (Figure ). Moreover, the curing and mechanical properties of MR y x -cured ENR could be facilely regulated via changing the structure and content of the cross-linkers, which could be able to meet industrial application requirements.…”
Section: Resultsmentioning
confidence: 99%
“…176 The global SBS system was valued at USD 35371.7 million in 2016 and is expected to grow at a compound annual growth rate of 6.97% to reach USD 5621.6 million by the end of 2023, providing a potential for the realm to grow in the coming years. Moreover, SBS can be modified to carboxylated SBS possessing superior physical and mechanical properties [177][178][179][180] that can further be tethered to shape memory property in developing robust elastomers with long-range deformation and excellent shape morphing behavior. This review aims to focus on the current state of the art of SBS-based shape memory polymers, attempting to comprehend the latest discoveries and outlooking the unexpected discoveries that shall unfold in the near future.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…3 Recently, SMPs and their composites have been applied in many fields including aerospace, 4−7 biomedicine, 8 textiles, 9−11 and electron devices. 12−14 So far, SMPs including polyurethane (PU), 15−17 cyanate, 18,19 epoxy, 20−22 polylactic acid, 23 polyimide, 24,25 polyaryletherketone, 26 and rubber 27,28 have been reported. However, the study of shape memory phenolformaldehyde (SMPF) resin is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The temporary shape can be maintained for a long time by cooling down below T trans and then the permanent shape can be automatically recovered upon reheating above T trans . Recently, SMPs and their composites have been applied in many fields including aerospace, biomedicine, textiles, and electron devices. So far, SMPs including polyurethane (PU), cyanate, , epoxy, polylactic acid, polyimide, , polyaryletherketone, and rubber , have been reported. However, the study of shape memory phenol-formaldehyde (SMPF) resin is rarely reported. , …”
Section: Introductionmentioning
confidence: 99%